Evaluating the Structure of Sluggish Cognitive Tempo Using Confirmatory Factor Analytic and Bifactor Modeling With Parent and Youth Ratings. (January 2018) - Smith, Zoe R.; Becker, Stephen P.; Garner, Annie A.; Rudolph, Cort W.; Molitor, Stephen J.; Oddo, Lauren E.; Langberg, Joshua M.
The primary goals of this study were to evaluate the dimensionality of the Penny et al. Sluggish Cognitive Tempo Scale and to compare model fits for parent- and youth self-report versions. Participants were 262 young adolescents (ages 10-15) comprehensively diagnosed with attention-deficit/hyperactivity disorder. Both confirmatory factor analysis (CFA) and bifactor modeling were used to determine if the proposed three-factor structure previously identified through exploratory factor analysis could be confirmed. Results showed that although the three-factor CFA had better fit statistics than a one- or two-factor CFA, the bifactor model was the best-fitting model for both parent report and self-report. This implies that Sluggish Cognitive Tempo Scale is best conceptualized as having an underlying general factor, with three specific factors that may represent different etiologies. Importantly, results also showed low-to-moderate correlations between raters and equivalent or better fit statistics for self-report in comparison with parent report.